2020
DOI: 10.3390/cells9040938
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 26 Skews Macrophage Polarization Towards M1 Phenotype by Activating cJUN and the NF-κB Pathway

Abstract: Interleukin 26 (IL-26) is a new member of the IL-10 family that is highly expressed in rheumatoid arthritis (RA). However, the functions of IL-26 produced by macrophages in RA have not been elucidated. In the present work, we evaluated the effects and the mechanisms of IL-26 on M1 and M2 macrophage differentiation. Human or mouse macrophage cells were treated with lipopolysaccharides (LPS), interferon gamma (IFNγ), or IL-4 alone or concurrently treated with IL-26 to monitor M1 or M2 macrophage subtypes. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Apart from the driving factor of oxidative damage, the STING and its downstream NF-κB are key molecules that mediate the pro-inflammatory response of macrophages ( Hou et al, 2018 ; Dunphy et al, 2018 ; Sun et al, 2020 ). The inflammatory response wherein macrophages is one of the essential contributors to their remodeling to the M1 phenotype ( Lin et al, 2020 ). In light of Ce6 PDT’s effect on the STING and subsequent NF-κB, we proceeded to investigate the role of the STING molecule in the PDT-mediated reprogramming of macrophages to establish a logical link between them thereupon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the driving factor of oxidative damage, the STING and its downstream NF-κB are key molecules that mediate the pro-inflammatory response of macrophages ( Hou et al, 2018 ; Dunphy et al, 2018 ; Sun et al, 2020 ). The inflammatory response wherein macrophages is one of the essential contributors to their remodeling to the M1 phenotype ( Lin et al, 2020 ). In light of Ce6 PDT’s effect on the STING and subsequent NF-κB, we proceeded to investigate the role of the STING molecule in the PDT-mediated reprogramming of macrophages to establish a logical link between them thereupon.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of NF-κB promotes the inflammatory response of macrophages on the one hand, thereby effectively changing them from a pro-tumor M2 phenotype to a pro-inflammatory, anti-tumor M1 phenotype. NF-κB is also a nuclear transcription factor that boosts the expression of a series of proteins such as iNOS and GBP5 ( Lin et al, 2020 ). These indicated that the STING molecule was centrally located in the PDT-mediated macrophage reprogramming process.…”
Section: Discussionmentioning
confidence: 99%
“…FLSs and macrophages produce IL-26 and IL-29, respectively. IL-26 can promote the polarization of M1 macrophages by activating the c-JUN/NF-kB/STAT1 signaling pathway and produce IL-6 and TNF-a pro-inflammatory factors (177). IL-29 is elevated in the serum of RA patients and participates in the chemotaxis of peripheral blood neutrophils, inhibits T follicular helper (Tfh) cell differentiation by reducing STAT3/BCL6 activity, and induces RANKL expression in FLSs through the MAPK pathway to participate in bone destruction.…”
Section: Interaction Of Cell Subsets and Cytokines In Rheumatoid Arthritismentioning
confidence: 99%
“…It is worth mentioning that IL-20R1 is restricted to epithelial cells and some myeloid cells, but IL-10R2 is ubiquitously expressed [13,14]. Although it has not been found any IL-26 orthologs in rodents, several murine cells have been confirmed to express the receptor for IL-26 and respond to its administration [15][16][17]. Upon IL-26 interaction with its receptor complex, it induces Janus kinase (JAK)1 and tyrosine kinase (TyK)2 signalling, which lead to phosphorylation and activation of signal transducer and activator of transcription (STAT)1 and STAT3 [11,12].…”
Section: Il-26 Receptor Structure and Signallingmentioning
confidence: 99%
“…IL-26 administration to monocyte cells activates NF-κB and cJUN transcription factors and differentiates these cells into STAT1-expressing CD80 + /CD86 + M1 macrophages that can produce IL-6 and TNF-α. In addition, the treatment of bone marrow-derived monocytes with IL-26 also skewed these cells towards the CD206 + / CD80 + M1 phenotype [17]. Other than immune response skewness in favour of RA, it has also been shown that IL-26 affects osteoclasts and promotes osteoclastogenesis.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%